2021
DOI: 10.1123/ijspp.2020-0300
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Active, Passive, and Combined Warm-Ups Among Junior Alpine Skiers in −7°C

Abstract: Context: Warming up in very cold climates and maintaining an elevated body temperature prior to a race is challenging for snow-sport athletes. Purpose: To investigate the effects of active (ACT), passive (PAS), and a combination of ACT and PAS (COM) warm-ups on maximal physical performance in a subzero environment among snow-sport athletes. Methods: Ten junior alpine skiers completed 3 experimental trials in −7.2 (0.2)°C. The ACT involved 5 minutes of moderate cycling, 3 × 15-second accelerations, a 6-second s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Physical quality can be divided into competitive physical quality and healthy physical quality. Competitive physical fitness refers to the body elements required by athletes to achieve excellent results in competitive competitions [20]. Hoffmann Jr. and others found that training to improve strength quality has a direct impact on the performance of tennis players.…”
Section: Related Workmentioning
confidence: 99%
“…Physical quality can be divided into competitive physical quality and healthy physical quality. Competitive physical fitness refers to the body elements required by athletes to achieve excellent results in competitive competitions [20]. Hoffmann Jr. and others found that training to improve strength quality has a direct impact on the performance of tennis players.…”
Section: Related Workmentioning
confidence: 99%
“…Other research investigating warm-ups in winter sport on subsequent performance indicate that a warm-up can positively influence body temperature in recreational alpine skiers, although it was not clear whether the skiing was completed in subzero conditions [ 96 ]. More recently, elite junior alpine ski racers were found to benefit from a warm-up that combined both active and passive (heated lower body garment) methods on cycling performance in −7 °C [ 97 ]. The authors interestingly ensured that the heated lower body garment was used in the transition period from end of warm-up to start of the cycling, to ensure maintenance of muscle temperature.…”
Section: Effects Of Cold Exposure On (Sport) Performancementioning
confidence: 99%
“…1 A recent study has shown that wearing a lowerbody heated garment following active WU improves performance and perceptual measures in alpine skiers in subzero temperatures, when compared to active or passive WU strategies alone. 30 Cross-country skiers' practices related to the transition period could therefore be improved. Currently, there is no research on the influence of passive heating strategies in XC skiing and this could be an impactful avenue for future research.…”
Section: Discussionmentioning
confidence: 99%